Targeting of Hepatic Macrophages by Therapeutic Nanoparticles - Colino, Clara I.; Lanao, José M.; Gutierrez-Millan, Carmen (Frontiers in Immunology, 2020)
Hepatic macrophage populations include different types of cells with plastic properties that can differentiate in a diversity of phenotypes to modulate their properties in response of different stimulus. They often regulate the activity of other cells and have an important role in many hepatic diseases. In response to those diseases, they are activated, releasing cytokines and chemokines; they may attract circulating monocytes and exert functions that can aggravate the symptoms or impulse reparation processes. Therefore, liver macrophages are potential therapeutic targets that can be oriented to a variety of aims and the emergent nanotechnology platforms may offer new perspectives for macrophages vectorization. Macrophages play an essential role in nanoparticle fate in the organism, as they are implied in their uptake and trafficking in vivo. Different types of delivery nanosystems for macrophage recognition and targeting such as liposomes and silica, solid-lipid or metallic nanoparticles have been developed. Passive targeting promotes the accumulation of the NPS in the liver due to their anatomical and physiological features. This process is modulated by NPs characteristics such as size, charge and surface modifications. Active targeting approaches with specific ligands can be used to reach liver macrophages. In order to design new particles, the recognition mechanism of NPs by macrophages must be understood, taking into account that variations in local microenvironment may change the phenotype of macrophages and this will impact on NPs uptake and toxicity. This kind of information may be applied to diseases were macrophages play a pathogenic role such as metabolic disorders. Kinetics of nanoparticles when administered in vivo strongly affects their therapeutic efficacy. Release kinetics could predict the nanosystems targeting macrophages behaviour and be applied to improve its characteristics. PBPK models have been developed to characterize nanoparticles biodistribution in organs of the reticuloendothelial system (RES) such as liver or spleen. Another controversial issue is the possible toxicity of non-degradable nanoparticles, that in many cases accumulate in high percentage in macrophage clearance organs such as the liver, spleen and kidney.